Analysis of using capacitors in 3-phase induction generators to get constant voltage - Mahdi Syukri (Geuthèë Institute, Aceh, 2023)
Induction machine is one of the machines that can be applied as an alternative power plant and also as a new renewable energy system. Giving reactive power at the terminal in the form of a capacitor, the induction machine can be used as an induction generator. Reactive power is also needed as a voltage generation process. Because one of the weaknesses of the induction generator is that the voltage generated is very fluctuating when the load being served changes. To overcome this, several capacitors with different values are used. Identify the value of the voltage generated by the induction generator when loading occurs by setting the required capacitor value. Setting the capacitor value is done by using a simulation of the simulink circuit in the MATLAB software. Based on the simulation of loading an induction generator of 6800 watt – 7500 watt different capacitor values are needed starting from 112 uF - 140 uF and to get a constant voltage value.